2008
DOI: 10.1369/jhc.2008.952044
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Apoptosis by Immunohistochemistry to Active Caspase-3, Active Caspase-7, or Cleaved PARP in Monolayer Cells and Spheroid and Subcutaneous Xenografts of Human Carcinoma

Abstract: Immunohistochemistry to active caspase-3, recently recommended for apoptosis detection, is inappropriate to detect apoptosis involving caspase-7. Cleavage of poly-ADP-ribose polymerase 1 (PARP-1), a major substrate of both caspases, is a valuable marker of apoptosis. Apoptosis evaluation induced in vitro either by paclitaxel or by photodynamic treatment (PDT) with Foscan in HT29 or KB monolayer cells and HT29 spheroids yielded a close percentage of labeled cells whatever the antibody used, whereas in control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(159 citation statements)
references
References 33 publications
10
147
0
2
Order By: Relevance
“…3G). Furthermore, immunohistochemical staining showed an increase in the number of cleaved PARP-positive tumor cells in tissue sections (18) from xenografted tumors containing KPNB1 shRNAs (Fig. 3H), further confirming that KPNB1 inhibition induces apoptosis both in vitro and in vivo, and providing a mechanism for its antitumor effect in EOC.…”
Section: Resultssupporting
confidence: 52%
“…3G). Furthermore, immunohistochemical staining showed an increase in the number of cleaved PARP-positive tumor cells in tissue sections (18) from xenografted tumors containing KPNB1 shRNAs (Fig. 3H), further confirming that KPNB1 inhibition induces apoptosis both in vitro and in vivo, and providing a mechanism for its antitumor effect in EOC.…”
Section: Resultssupporting
confidence: 52%
“…Apoptosis was also assessed in tumor sections by immunostaining for active caspase-3, using anti-cleaved caspase-3 (Asp175) antibody (1:2,000 dilution; Cell Signaling, New England Bioloabs, UK) as previously described. 37 Apoptotic cells were quantified using a 10 Â 10 ocular graticule (total area 1 mm 2 ) using a 20Â objective in 5 random fields of view, avoiding necrotic regions. Data were expressed as the mean number of apoptotic cells/mm 2 .…”
Section: Measurement Of Tumor Cell Apoptosismentioning
confidence: 99%
“…It had been reported that apoptotic pathways may be initiated [9][10][11][12], however, autophagy or necrosis [13] may prevail -especially if high PDT doses are applied [14].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, effects may not only include activation of caspase cascades [10,11] but also acute-phase response processes [15], and expression changes of heat-shock proteins [16], hypoxiamarkers [17], matrix metalloproteinases [18] or cytokines [19]. Since some of these cellular responses may modify, delay or even counteract cell death mechanisms, detailed analyses are highly needed.…”
Section: Introductionmentioning
confidence: 99%